2020
DOI: 10.1111/1751-7915.13566
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol affects in vitro rumen fermentation, methane production and prokaryotic community composition in a time‐ and diet‐specific manner

Abstract: This study aimed to investigate the effect of resveratrol on methane production, rumen fermentation and microbial composition under high-concentrate (HC) and high-forage (HF) diets using the in vitro fermentation system. A total of 25 mg of resveratrol was supplemented into 300 mg of either HC or HF diet. Methane production, total volatile fatty acid (VFA) concentration, molar proportion of VFA, metabolites of resveratrol and prokaryotic community composition were measured after 12 and 24 h of in vitro ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 58 publications
4
16
0
Order By: Relevance
“…However, little is known about this microorganism. Ma et al [ 56 ] reported that Gastranaerophilales is capable of fermenting a range of sugars (e.g., glucose, starch, and hemicellulose) to produce butyrate in the gut of herbivores. Borsanelli et al [ 57 ] found that the abundance of Gastranaerophilales was higher in the mouths of healthy cattle and lower in the mouths of cattle with bovine periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about this microorganism. Ma et al [ 56 ] reported that Gastranaerophilales is capable of fermenting a range of sugars (e.g., glucose, starch, and hemicellulose) to produce butyrate in the gut of herbivores. Borsanelli et al [ 57 ] found that the abundance of Gastranaerophilales was higher in the mouths of healthy cattle and lower in the mouths of cattle with bovine periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…A common issue with all in vitro experiments is the paucity of in vivo data. However, it must be noted that in vitro techniques can provide satisfactory accuracy for comparative purposes and precludes unnecessary in vivo experimentation [ 22 , 23 ]. Therefore, we used an in vitro experiment to investigate the effects of supplementation of AOAN on nutrient degradation of a total mixed ration (TMR), three different roughages (corn silage, oat hay, and alfalfa hay), at four-time points (7 h, 24 h, 30 h, and 48 h).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the research on RES in ruminants has mainly focused on its impact on methane emissions and rumen fermentation [ 18 , 19 ]. Wang et al (2020) found that RES mitigated methane production in in vitro fermentation techniques, which may be related to a decreased abundance of Methanobrevibacter [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to clarify the effects of dietary RES on rumen fermentation and rumen microbiota. However, previous studies on RES in ruminants mainly focus on its impact on methane emissions [ 18 , 19 ], whilst the effects of dietary RES supplementation on the rumen microbiota of fattening goats have not been reported.…”
Section: Introductionmentioning
confidence: 99%